O processo decisório legislativo e o preceito constitucional de igualdade: uma análise da atuação da Frente Parlamentar da Agropecuária (FPA) na concepção da política fundiária brasileira - Graciano, Monyele Camargo (Universidade Federal de São Carlos, 2022)
This research refers to the analysis of the way in which a legislative framework can guarantee or distort the application of the constitutional principle of equality between individuals during the legislative decision-making process. The 1988 constitutional text contemplates the rights and guarantees that promote the well-being of all, without distinction of origin, race, sex, color, age. In turn, the political participation of minority groups still does not represent the structural reality of Brazilian society, thus, in this research, a verification of this scenario in an approach to the formulation of Brazilian land policy, resulting from the legal process and, historically permeated by the predilections of a rural elite, which in 2008 was consolidated in the Agricultural Parliamentary Front (FPA), to the detriment of the interests of others involved. Thus, the objective of this research was to verify how the legislative institutional framework can guarantee or distort the application of the constitutional principle of equality between individuals in the course of their decision-making process, taking into account the performance of interest groups. In this sense, the methodology was based on the investigation of the following categories of analysis: i) the structure of the land policy legislative process, based on the proceedings in the National Congress; ii) legislative proposals that dealt with rural land policy between 2008 and 2018, under the interests of the Agricultural Parliamentary Front (FPA); iii) the role of FPA members in the land policy decision-making process. From these analyses, it was possible to understand to what extent the FPA manages to foster conditions that enable the success of its demands through the legislative institutional arrangement, acting in the defense of sectoral interests and in strategic positions in the decision-making process of land policy aiming to promote the defense of rural interests to the detriment of the other beneficiaries of such a policy.
The legislative decision-making process and the constitutional precept of equality: an analysis of the performance of the Parliamentary Agricultural Front (FPA) in the conception of brazilian land policy
Keywords: Processo decisório; Princípio da igualdade; Frente Parlamentar da Agropecuária; Agronegócio; Política fundiária; CIENCIAS HUMANAS::CIENCIA POLITICA::TEORIA POLITICA